Cyclic di-GMP regulates bacterial colonization and further biocontrol efficacy of Bacillus velezensis against apple ring rot disease via its potential receptor YdaK - Gong, Huiling; Jiang, Wenxiao; Yang, Yang; Zhang, Yue; Chen, Xufei; Li, Wei; Yang, Panlei; Wang, Zhenshuo; Wang, Qi; Li, Yan (Frontiers in Microbiology, 2022)
Bacillus species are considered important biological control agents and preferred in agricultural systems. Its biocontrol efficacy was controlled by diverse regulators. Cyclic diguanylate (c-di-GMP) is a near universal second messenger in bacteria and modulates various physiological processes important for bacteria, including motility, biofilm formation, antifungal antibiotic production and host colonization. However, the impact of c-di-GMP on biocontrol efficacy of beneficial bacteria is unknown. Bacillus velezensis PG12 is an effective beneficial strain against apple ring rot disease caused by Botryosphaeria dothidea. In this study, the contribution of c-di-GMP to biocontrol efficacy of B. velezensis PG12 was investigated. Deletion of single gene encoding diguanylate cyclase or phosphodiesterase did not affect its biocontrol efficacy against apple ring rot. However, artificially elevated or decreased c-di-GMP level in the cells leads to a significant change of biocontrol efficacy, suggesting that c-di-GMP positively regulates biocontrol efficacy of B. velezensis PG12 against apple ring rot disease. More evidences indicate that c-di-GMP does not affect antagonistic activity of B. velezensis PG12 to B. dothidea in vitro and in vivo, but positively regulates biofilm formation. More evidences showed that the potential c-di-GMP receptor YdaK regulates biofilm formation and biocontrol efficacy but not antagonistic activity of B. velezensis PG12 in the low c-di-GMP level background. Importantly, deletion of ydaK could rescue the inhibition of biofilm formation and biocontrol efficacy by low c-di-GMP level, indicating that YdaK is the potential c-di-GMP receptor to regulate biofilm formation and effective biological control. Based on these findings, we propose that c-di-GMP regulates biofilm formation and further biocontrol efficacy of B. velezensis through its receptor YdaK. This is the first report showing that c-di-GMP plays a role in biocontrol efficacy of beneficial bacteria.